2022
DOI: 10.14366/usg.21186
|View full text |Cite
|
Sign up to set email alerts
|

Transcutaneous application of ultrasound enhances the effects of finasteride in a murine model of androgenic alopecia

Abstract: Purpose: The purpose of this study was to evaluate if transcutaneous application of low-intensity ultrasound can locally enhance the effects of finasteride on hair growth in a murine model of androgenic alopecia (AA).Methods: AA mice (injected twice per week with testosterone enanthate, n=11), under daily oral administration of finasteride, received 1-MHz ultrasound for 1 hour at the unilateral thigh area five times per week for 5 weeks. Non-thermal and non-cavitational ultrasound was delivered in a pulsed man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…The percentage of hair follicles in anagen per telogen was markedly increased in YH complex‐treated mice. Regarding this, there are researches that topical application as well as oral administration of finasteride increased hair follicle anagen/telogen ratio (Kim et al., 2022). From those results, YH complex was found to have hair growing effects as similar as finasteride in AGA, although the components, doses, treatment period, and route are different.…”
Section: Discussionmentioning
confidence: 99%
“…The percentage of hair follicles in anagen per telogen was markedly increased in YH complex‐treated mice. Regarding this, there are researches that topical application as well as oral administration of finasteride increased hair follicle anagen/telogen ratio (Kim et al., 2022). From those results, YH complex was found to have hair growing effects as similar as finasteride in AGA, although the components, doses, treatment period, and route are different.…”
Section: Discussionmentioning
confidence: 99%
“…Considering a 50% duty cycle of sonication, the spatial-peak temporal-average intensity (I SPTA ) was 2.5 W/cm 2 . The use of a 50-ms pulse duration and a 10-Hz pulse repetition frequency was based on a non-thermal pulsing scheme that has been shown to unbind phenytoin from albumin at 250 kHz (12) and unbind lidocaine from α-1-acid glycoprotein at 500 kHz (13). Additional equilibrium dialysis cassettes were placed outside the sonication path (Figure 1E, 'FO') and in a region that was not exposed to sonication (Figure 1E, 'C' condition).…”
Section: Methodsmentioning
confidence: 99%
“…Application of non-ionizing, non-thermal mechanical force generated by pulsed low-intensity ultrasound pressure waves to the drug-plasma protein complex was found to temporarily disrupt PPB, consequently increasing the amount of unbound ('free') drug molecules available to the tissue without elevating the systemic concentration (12)(13)(14)(15). Investigations have revealed that acoustic pressure waves applied to a local region of tissue (of the order of 400 kPa) can impose a non-thermal radiation force greater than the binding force [Kim et al (13) for theoretical derivations for albumin and α-1-acid glycoprotein], leading to temporary unbinding of a drug from plasma proteins, which raises its 'effective' unbound concentration.…”
mentioning
confidence: 99%